1997
DOI: 10.1046/j.1365-2141.1997.752711.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal chromosomal abnormalities as direct evidence for clonality in nasal T/natural killer cell lymphomas

Abstract: Nasal T/natural killer (NK) cell lymphoma is a distinct clinicopathologic entity which is more prevalent in Asia than in America and Europe. The clonal nature of the infiltrating lymphoid cells is difficult to demonstrate because of the lack of immunologic markers for clonality and the absence of clonal T‐cell receptor gene rearrangement in most cases. In this study, clonal chromosomal abnormalities were detected in the tumour cells from four patients with nasal T/NK cell lymphoma. This finding provided direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 17 publications
3
43
1
Order By: Relevance
“…26 Using probes specific for the centromeric region and the long arm of the chromosome 6, we found that one case showed a pattern highly suggestive for the presence of an isochromosome 6p. This aberration is very common in human retinoblastoma, 27 but has also been reported in approximately 1% of acute lymphoblastic leukemia 28 and Hodgkin's lymphoma 29 and in 6% of primary mediastinal 30 and gastric NHLs, 25 as well as in individual cases of follicular, 10 nodal diffuse large B-cell 31 and nasal T/NK NHLs 32 and of Waldenstrom's macroglobulinemia. 33 It has been suggested that, similarly to cyclin D1 in mantle cell lymphoma and plasma cell myeloma, cyclin D3 may be deregulated in hematopoietic disorders as a consequence of the t(6;14) translocation.…”
Section: Discussionmentioning
confidence: 93%
“…26 Using probes specific for the centromeric region and the long arm of the chromosome 6, we found that one case showed a pattern highly suggestive for the presence of an isochromosome 6p. This aberration is very common in human retinoblastoma, 27 but has also been reported in approximately 1% of acute lymphoblastic leukemia 28 and Hodgkin's lymphoma 29 and in 6% of primary mediastinal 30 and gastric NHLs, 25 as well as in individual cases of follicular, 10 nodal diffuse large B-cell 31 and nasal T/NK NHLs 32 and of Waldenstrom's macroglobulinemia. 33 It has been suggested that, similarly to cyclin D1 in mantle cell lymphoma and plasma cell myeloma, cyclin D3 may be deregulated in hematopoietic disorders as a consequence of the t(6;14) translocation.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, there is ample evidence which implicates the role of genes around the flanking region of the break/fusion points in distinct phenotypes of many hematological disorders [4,[26][27][28][29]41]. For examples, 5p13 deletion is one of the most common regions emerging in acute lymphoblastic leukemia, lymphoblastic lymphoma, acute monoblastic leukemia, acute myleoblastic leukemia with maturation, acute myeloid leukemia, adult T-cell lymphoma/ leukemia, chronic lymphocytic leukemia, etc [4,24,25,[41][42][43][44][45]. Despite a strong implication for genes located in 5p, the molecular mechanisms underlying their deregulation in these characteristic disorders still remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of the long arm of chromosome 6 (6q) are one of the most common chromosomal abnormalities observed in various human solid (Orphanos et al, 1995;Noviello et al, 1996;Theile et al, 1996;Makino et al, 2001;Piao et al, 2001) and lymphoid malignancies (Gerard et al, 1997;Sherratt et al, 1997;Tien et al, 1997;Wong et al, 1997;Hauptschein et al, 1998;Merup et al, 1998;Amiel et al, 1999;Stilgenbauer et al, 1999;Sinclair et al, 2000;Mancini et al, 2002). Many subchromosomal regions from 6q13 to q27 have been suggested to harbour putative tumour suppressor genes for different types of tumours, examples being 6q14-21 in prostate cancer (Cooney et al, 1996), 6q16-q21 in lymphoid leukaemia (Jackson et al, 1998(Jackson et al, , 2000, 6q23.3-q25 in breast cancer, and 6q27 in B-cell non-Hodgkin lymphoma (NHL) (Hauptschein et al, 1998) and ovarian cancers (Saito et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using various techniques have reported chromosomal abnormalities in NK/T-cell lymphoma/leukaemia patients; these include gains on chromosomes Xp,8 and 20p, and deletions on 6q, 11q, 13q and 17q (Tien et al, 1997;Wong et al, 1997;Siu et al, 1999;Wong et al, 1999a;Zhang et al, 1999;Ko et al, 2001). Of these, deletion at 6q21-q25 is the most common chromosomal abnormality (Wong et al, 1997;Zhang et al, 1999), occurring in more than 90% of patients with nasal NK/T-cell lymphoma (Siu et al, 2000).…”
mentioning
confidence: 99%